Yield and Nuse efficiency of five tropical maize genotypes under different N levels in the moist savanna of Nigeria - Oikeh, S.O.; Kling, J.G.; Horst, Walter J.; Chude, V.O. (1997)
Two field experiments were conducted during the 1993 and 1994 growing seasons at Samaru (7° 38' E; 11° 11' N), northern Nigeria, to evaluate N-use efficiency (kg grain per kg available soil N) and yield of 5 maize genotypes planted early in the season under five levels of N. The hybrid (8644-27) gave the highest grain yield and was the most N-use efficient genotype. It had a longer grain filling period, a higher harvest index, and a greater 1000-kerneI weight than other genotypes. The most widely grown open pollinated variety (TZB-SR) was the least efficient in utilizing available soil N for grain production, although it had the highest number of kernels per ear and total above-ground dry matter. The semiprolific (SPL) and EV8728-SR genotypes appeared to have a higher potential to adapt to nitrogen stress than other genotypes. They had higher grain yields under zero-N in both years, but the differences were not significant. They also showed greater synchronization of anthesis and silking, which indicates better ability to tolerate nitrogen stress. Traits such as extended grain filling and 1000-kernel weight should be further investigated for inclusion in a breeding scheme to increase maize yield. Early planting to capture the N flush, and application of a suboptimal amount of N (60 kg/ha at 2 WAP) was adequate for production of all the genotypes under the loamy soil conditions of the chosen site. A combination of legume rotation, 60 kg N/ha, and an N-use efficient genotype (8644-27) gave a yield advantage of 1.3 t/ha over a monocrop maize supplied with 60 kg N/ha on farmers' fields in the moist savanna of Nigeria.